Optimizing Cardiorespiratory Function among Older Adults through the GERLAPKOTA with MPD Program at UPT Pelayanan Sosial Tresna Werdha Jombang - Ifa Gerhanawati; Hafizah Sururul Nur Rakhmawati; Ervina Ayu Permata Sari (Jurnal Pemberdayaan Masyarakat dan Komunitas, 2026)
Age-related physiological changes contribute to a decline in respiratory function through reduced lung elasticity, respiratory muscle strength, and thoracic mobility. This community service program aimed to enhance older adults' knowledge and skills in performing breathing exercises to support cardiorespiratory health. The program was conducted in November 2025 at UPT Pelayanan Sosial Tresna Werdha Jombang and involved 25 older adults. Activities included health education, demonstration and supervised practice of MPD breathing techniques (pursed-lip breathing, diaphragmatic breathing, and thoracic breathing exercise), descriptive thoracic expansion assessment, and interactive discussions. Participants actively engaged throughout the program and successfully performed the breathing techniques under supervision. Mean thoracic expansion was 2.88 ± 0.91 cm at the axillary level and 2.56 ± 1.47 cm at the xiphoid level. The program demonstrated good feasibility and acceptability as a community-based physiotherapy intervention to promote respiratory health among older adults.